2015
DOI: 10.1149/2.0431603jes
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Pure Aluminium and Alloys AA2024-T3 and AA7075-T6 by Cerium(III) and Cerium(IV) Salts

Abstract: The corrosion protection of pure aluminium and its alloys AA2024-T3 and AA7075-T6 has been studied in 0.1 M NaCl with and without the addition of Ce(III) chloride, Ce(III) nitrate, Ce(III) acetate and Ce(IV) sulfate. The study of Ce(III) acetate has been scarce but is here shown to be the most effective of the cerium salts studied, especially for AA7075-T6. The inhibition effectiveness of cerium salts is: Ce(III) acetate > Ce(III) chloride > Ce(III) nitrate for the metals studied. Ce(IV) sulfate does not inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 64 publications
(167 reference statements)
3
67
0
Order By: Relevance
“…The authors showed that most of the OIH coatings developed were for aluminum-based alloys followed by iron-based alloys. Nowadays, the tendency reported for aluminum-based alloys seems to be maintained [215][216][217][218][219][220]. Moreover, in the last decade, considerable attention has been given to the development of advanced and multifunctional OIH sol-gel coating materials.…”
Section: [138]mentioning
confidence: 99%
“…The authors showed that most of the OIH coatings developed were for aluminum-based alloys followed by iron-based alloys. Nowadays, the tendency reported for aluminum-based alloys seems to be maintained [215][216][217][218][219][220]. Moreover, in the last decade, considerable attention has been given to the development of advanced and multifunctional OIH sol-gel coating materials.…”
Section: [138]mentioning
confidence: 99%
“…It is known that the deposition of Ce-oxides proceeds at the cathodic sites at the surface which are, in the case of AA7075-T6, Cu-containing intermetallic particles (IMPs). [54][55][56][57][58][59] The fact that no Cu could be identified at the intermetallic particles proves that the deposits of Ce hydroxide/oxide are thicker than is the EDS analysis depth, i.e. several micrometers.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, all the studied inhibitors decreased the rate of both the anodic and cathodic processes. Rodič and Milošev (2016) have carried out a study on the inhibition effects of Cerium (III) and Cerium (IV) Salts on pure aluminum and Alloys AA2024-T3 and AA7075-T6 in 0.1 M NaCl. Electrochemical potentiodynamic measurements were used to study inhibition effectiveness of cerium salts.…”
Section: Corrosion Inhibition Of Aluminium Alloysmentioning
confidence: 99%